Poziom ekonomiczny gospodarstwa w różnych fazach rozwoju rodziny chłopskiej - Adamczyk, Jolanta (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 1996)
The aim here is to examine relations between the economic level of family farm and the peasant family development stages. In the family and farm development we may distinguish certain stages having a cyclic character. Here it is proved that a change in the age of farm leader, numbers and family composition in successive development stages produce changes in family needs and thus changes the economic activity of farmers. And so capital resources, production and economic effects and forming effectiveness also change in successive distinguished five phases of family development.